Pendampingan Kepala Sekolah dalam Pengembangan Supervisi Akademik melalui Bimbingan Pelatihan di Era Kurikulum Merdeka - Suroso, Suroso (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
This paper aims to present a structured plan to support school principals in developing academic supervision programs through targeted training in the "Kurikulum Merdeka" era. The mentoring process consists of two main stages. Stage 1 begins with Pre-Action activities, which include identifying the current condition of the school's academic supervision program, scheduling mentoring sessions, preparing academic supervision plans, and designing supervision instruments to review program documentation. The Action phase includes explaining the supervision planning process, discussing implementation strategies, simulating program development, and completing relevant supervision instruments. Reflection activities involve evaluating the mentoring process and formulating steps for Stage 2, enabling principals to plan, implement, evaluate, and report on academic supervision effectively. Stage 2 begins with preparing sample documents for supervision plans, implementation, analysis, evaluation, and reporting. The Action phase includes group simulations on designing supervision programs, using supervision instruments (covering planning, implementation, and assessment), and analyzing results with sample documentation and attendance evidence. The Reflection phase includes evaluating the overall mentoring process and developing real action plans for academic supervision during both semesters. In conclusion, the mentoring program significantly enhances school principals’ competencies in executing academic supervision aligned with the objectives of the “Kurikulum Merdeka.”